The OARSI Joint Effort Initiative: Priorities for osteoarthritis management program implementation and research 2024–2028 - Bowden, Jocelyn L.; Hunter, David J.; Mills, Kathryn; Allen, Kelli; Bennell, Kim; Briggs, Andrew M.; Dziedzic, K.; Hinman, Rana S.; Kim, Jason S.; Martinez, Nina; Quicke, Jonathan G.; Tan Yijia, Bryan; et al. (Osteoarthritis and cartilage open, 2023)
The Joint Effort Initiative (JEI) is an international collaboration of clinicians, researchers, and consumer organisations with a shared vision of improving the implementation of osteoarthritis management programs (OAMPs). This study aimed to identify JEI's future priorities and guide direction. A two-part international survey to prioritise topics of importance to our membership and research stakeholders. Survey one presented a list of 40 topics under 5 themes. Consenting participants were asked to choose their top three topics in each theme. A short list of 25 topics was presented in survey two. Participants were asked to rank the importance (100-point NRS scale, 100 ​= ​highest priority). Response frequency (median, IQR) was used to rank the top priorities by theme. Ninety-five participants completed survey one (61% female, 48% clinicians) and 57 completed survey two. The top ranked topic/s were: i. Promotion and advocacy: support training for health professionals (median 85, IQR 24). ii. Education and training: incorporating behaviour change into OAMPs (80, 16), advanced OA skills (80, 30), and integration of OA education into clinical training (80, 36). iii. Improving OAMPs delivery: regular updates on changes to best-evidence OA care (84, 24). iv. Future research: improve uptake of exercise, physical activity, and weight-loss (89, 16). v. Enhancing relationships, alliances, and shared knowledge: promote research collaborations (81, 30), share challenges and opportunities for OAMP implementation (80, 23). These topics will set the JEI's research and collaboration agenda for the next 5 years and stimulate ideas for others working in the field.